Information policies: development and strategies from EU programmes and their impact in Spain - Martínez Pestaña, María Jesús (Revista General de Información y Documentación, 2013)
This study describes the information policies from the European Union and their impact on the design of Spanish information policies. It is noted the split between a model based on efficiency and quality from the EU, and a critical economic and social context since 2010 in Spain, especially in the seventh Framework Programme lasting until 2013. By one hand, the European Union has encouraged the development of specific instruments concerning information policies, such as various consortia, Eureka and ESPRIT (European Strategic Programme for Research in Information Technologies), and the subsequent periodical programs named Framework Programmes. This frame has facilitated the creation of Spanish institutions as REBIUN (Red de Bibliotecas Universitarias), FECYT (Fundación Española para la Ciencia y la Tecnología), and the recently created Agencia Estatal de Investigación (AEI) (June 2012). By other hand, the information policies scheme from the European Union points out the aspirations of the European Union to stand up geographically, technologically and strategically as a role model compared to other strong regions as North America and Japan, as could be proved by the Agenda Digital 2010, first initiative under the strategic target Europe 2020.
Keywords: Information policy; information society; European Union strategy